Capsule Endoscopy in Refractory Diarrhea-Predominant Irritable Bowel Syndrome and Functional Abdominal Pain - Manuel Valero; Gladys Bravo-Velez; Roberto Oleas; Miguel Puga-Tejada; Miguel Soria-Alcívar; Haydee Alvarado Escobar; Jorge Baquerizo-Burgos; Hannah Pitanga-Lukashok; Carlos Robles-Medranda (Korean Society of Gastrointestinal Endoscopy, 2018)
Background/Aims Capsule endoscopy is a diagnostic method for evaluating the small bowel lumen and can detect undiagnosed lesions. The aim of this study was to evaluate the diagnostic yield and clinical impact of capsule endoscopy in patients with refractory diarrhea-predominant irritable bowel syndrome and functional abdominal pain. Methods This study involved a retrospective analysis of prospectively collected data, maintained in a database. Patients with refractory diarrhea-predominant irritable bowel syndrome and functional abdominal pain within the period of March 2012 to March 2014 were included. Capsule endoscopy was used to detect small bowel pathologies in both groups. Results Sixty-five patients (53.8% female) fulfilled the inclusion criteria and had a mean (±standard deviation) age of 50.9±15.9 years. Clinically significant lesions were detected via capsule endoscopy in 32.5% of the patients in the abdominal pain group and 54.5% of the patients in the diarrhea group. Overall, 48% of patients had small bowel pathologies detected during the capsule endoscopy study. Inflammatory lesions and villous atrophy were the most frequent lesions identified in 16.9% and 15.3% of patients in the abdominal pain and the diarrhea groups, respectively. Conclusions Routine use of capsule endoscopy in patients with irritable bowel syndrome should not be recommended. However, in patients with refractory conditions, capsule endoscopy may identify abnormalities.